Basic researchGlial cell line-derived neurotrophic factor enhances the invasive ability of pancreatic cancer cells by regulating urokinase-type plasminogen activator and matrix metalloproteinase - Funahashi, Hitoshi; Sawai, Hirozumi; Yasuda, Akira; Ochi, Nobuo; Takahashi, Hiroki; Matsuo, Yoichi; Wakasugi, Takehiro; Takeyama, Hiromitsu (Archives of Medical Science, 2007)
Introduction: Tumour invasion and metastasis consist of multiple steps involving changes in proliferation, motility, adhesion, invasion, and secretion of certain enzymes. Cancer cell invasion calls for the action of several proteinases that degrade the extracellular matrix and basement membranes. For several decades, matrix metalloproteinases (MMP) have been thought to be cancer-related proteinases, and recent reports have revealed that the plasminogen activator (uPA) system plays an important role in cancer cell viability. Material and methods: The casein zymography procedure was used to determine uPA activity in the human pancreatic cancer cell lines BxPC-3, HPAF-II, and MIA PaCa-2. Gelatinase activity of cell culture supernatants was determined by gelatin zymography. Proliferation of pancreatic cancer cells was monitored using an MTT assay and cell counting. Invasive behavior was examined using a Matrigel double-chamber assay. Results: The uPA activity of HPAF-II cells was the strongest of all the cells examined, and HPAF-II only showed both high molecular weight (HMW) and low molecular weight (LMW) uPA. GDNF enhanced the invasive ability of pancreatic cancer cells that expressed the components of the plasminogen activator system. This effect was inhibited by a specific uPA inhibitor. Furthermore, GDNF increased MMP activities, and the uPA inhibitor partially inhibited MMP activities. Conclusions: The present study suggests that the plasminogen activator system plays an essential role in pancreatic cancer cell invasion. Activation of uPA by GDNF enhanced the invasive ability of pancreatic cancer cells and also increased the expression of active MMPs.